Melampaui Dilema Keamanan: Penjelasan Multitingkat mengenai Perang Rusia melawan Ukraina dan Penataan Ulang Keamanan Eropa, 2014–2026 - Riswanda Imawan (Universitas Muhammadiyah Sumatera Utara, 2026)
Why did Russia escalate a conflict that began in 2014 into a full-scale invasion of Ukraine in February 2022, and how do the war's consequences through 2026 alter the evaluation of its underlying motives? This article develops a multi-level explanation that combines structural security competition, domestic regime security, imperial identity narratives, geostrategic interests in Crimea and the Black Sea, and geoeconomic leverage. Using a qualitative explanatory case study and process tracing of critical developments from 1991 to 2026, the analysis draws on official documents, public speeches, international-organization reports, and peer-reviewed scholarship. The article argues that NATO enlargement and the contested post-Cold War security order created a permissive security dilemma but did not mechanically cause the invasion. Escalation required the interaction of structural rivalry with an increasingly personalized authoritarian decision process, narratives that denied Ukraine's autonomous nationhood, and expectations that coercive force could reverse Ukraine's Western orientation at acceptable cost. Energy interdependence strengthened Moscow's leverage and fiscal capacity, functioned primarily as an instrument rather than an independent root cause. The timing of the 2022 invasion reflected a severe misreading of Ukrainian resilience, Western cohesion, and the feasibility of a rapid political settlement imposed by force. By 2026, the war had generated substantial strategic blowback: NATO expanded to Finland and Sweden, Ukraine's European integration advanced, and the European Union institutionalized a deeper reduction of Russian energy dependence. The article contributes by distinguishing enabling conditions, decision mechanisms, and post-invasion consequences, thereby moving beyond single-cause explanations and retrospective justifications.Why did Russia escalate a conflict that began in 2014 into a full-scale invasion of Ukraine in February 2022, and how do the war's consequences through 2026 alter the evaluation of its underlying motives? This article develops a multi-level explanation that combines structural security competition, domestic regime security, imperial identity narratives, geostrategic interests in Crimea and the Black Sea, and geoeconomic leverage. Using a qualitative explanatory case study and process tracing of critical developments from 1991 to 2026, the analysis draws on official documents, public speeches, international-organization reports, and peer-reviewed scholarship. The article argues that NATO enlargement and the contested post-Cold War security order created a permissive security dilemma but did not mechanically cause the invasion. Escalation required the interaction of structural rivalry with an increasingly personalized authoritarian decision process, narratives that denied Ukraine's autonomous nationhood, and expectations that coercive force could reverse Ukraine's Western orientation at acceptable cost. Energy interdependence strengthened Moscow's leverage and fiscal capacity, functioned primarily as an instrument rather than an independent root cause. The timing of the 2022 invasion reflected a severe misreading of Ukrainian resilience, Western cohesion, and the feasibility of a rapid political settlement imposed by force. By 2026, the war had generated substantial strategic blowback: NATO expanded to Finland and Sweden, Ukraine's European integration advanced, and the European Union institutionalized a deeper reduction of Russian energy dependence. The article contributes by distinguishing enabling conditions, decision mechanisms, and post-invasion consequences, thereby moving beyond single-cause explanations and retrospective justifications.